The legal limits of higher education internationalization in Ukraine - Dikhtiaruk, A. B. (Аналітично-порівняльне правознавство, 2025)
The article presents a comprehensive legal study of the process of internationalization of higher education in Ukraine through the prism of determining its regulatory boundaries, potential risks and legal guidelines for development. The scientific study of the topic is because internationalization is not only a strategic vector of development of the educational sphere in the 21st century, but also a tool for increasing the competitiveness of national universities, integrating Ukraine into the European educational space and modernizing the higher education system. The paper describes the legal principles of internationalization enshrined in the current legislation of Ukraine, in the Laws «On Higher Education» and «On Education», as well as in subordinate regulatory legal acts, in particular, Resolution of the Cabinet of Ministers of Ukraine No. 579 of August 12, 2015. It is emphasized that these documents provide a regulatory basis for the implementation of academic mobility, the introduction of double degree programs, the introduction of English-language training and the development of joint educational projects with foreign partners. It is established that Ukraine’s participation in the Bologna Process, the implementation of the provisions of the Lisbon Convention and the Association Agreement with the EU have provided the regulatory framework for internationalization with a multi-level structure, combining imperative norms of international law, national legislation and university self-regulation. The article reveals the main institutional forms of internationalization: academic mobility, double degree programs, joint research projects, participation in international rankings, and teaching in foreign languages. It is emphasized that internationalization is not a neutral or automatically positive phenomenon. The article provides a thorough legal analysis of the challenges and risks that accompany this process. Among them: excessive standardization of educational programs under the influence of external models, legal diffusion and conflicts of jurisdictions, the outflow of intellectual capital, the depreciation of the national cultural component in higher education, inequality of access to international opportunities, as well as the risks of excessive commercialization and quality reduction in the conditions of global competition. It is substantiated that legal regulation should provide mechanisms that can minimize these risks, while maintaining openness to international cooperation. It has been established that the key legal mechanism that outlines the boundaries of internationalization is the principle of autonomy of higher education institutions. It is autonomy, combined with normatively defined guarantees of state control over the quality of education and compliance with language policy, that creates a balanced basis for the functioning of an open but sovereign system of higher education. It has been determined that excessive state intervention in internationalization processes, as well as complete liberalization without proper regulatory supervision, can have destructive consequences for the educational sovereignty of Ukraine. As a result, the need to develop a holistic doctrine of balanced internationalization is substantiated, which would combine imperative mechanisms for protecting the national interest with institutional flexibility and openness to international practices. It is summarized that internationalization should be perceived not as a threat, but as a tool for strengthening national intellectual potential, if there are clear legal boundaries, effective control mechanisms and a strategic vision at the level of state policy.